The Yeast C-Type Cyclin Ctk2p Is Phosphorylated and Rapidly Degraded by the Ubiquitin-Proteasome Pathway - Hautbergue, Guillaume (American Society for Microbiology, 1999)
The yeast CTDK-I complex has been implicated in phosphorylation of the carboxy-terminal domain of the RNA polymerase II and in transcription control. It is composed of three polypeptides: Ctk1p and Ctk2p, a cyclin-dependent kinase and a C-type cyclin subunit, respectively; and Ctk3p, a third subunit of unknown function. Cyclins are regulatory proteins whose expression is tightly controlled at the protein level. In this study, we examined the regulation of Ctk2p expression in vivo. Surprisingly, unlike what has been described for cell cycle cyclins, steady-state levels of Ctk2p are composed of two relatively abundant forms, one of them phosphorylated. We show that this phosphorylated form is extremely unstable (half-life, 5 min) and that rapid proteolysis of Ctk2p exhibits growth-related regulation. Furthermore, our data establish that similar to the case for other naturally short-lived proteins, Ctk2p degradation is mediated by the ubiquitin-proteasome pathway. This is the first demonstration that a C-type cyclin is phosphorylated and targeted to the proteasome. Strikingly, neither phosphorylation nor destruction of Ctk2p requires its associated kinase Ctk1p, a feature fundamentally different from that which has been observed for cell cycle cyclins.